Cu- or Ag-containing Bi-Sb-Te for in-line roll-to-roll patterned thin-film thermoelectrics - Xudong Tao; Qianfang Zheng; Chongyang Zeng; Harry Potter; Zheng Zhang; Joshua Ellingford; Ruy S. Bonilla; Emiliano Bilotti; Patrick S. Grant; Hazel E. Assender (Nature Communications)
Abstract The Selective Metallization Technique shows promise for roll-to-roll in-line patterning of flexible electronics using evaporated metals, but challenges arise when applied to sputtering functional materials. This study overcomes these challenges with simultaneous sputtering of Bi-Sb-Te and evaporation of metal (Ag or Cu) for thermoelectric layers when using Selective Metallization Technique. Large-scale manufacturing is demonstrated through roll-to-roll processing of a 0.8 m wide polymer web at 25 m/min, achieving high-throughput production of functional thin-film patterns with nanometer thickness. The room-temperature-deposited material system exhibits significantly enhanced thermoelectric performance and facilitates an n-type-to-p-type transition in the Cu- or Ag-containing Bi-Sb-Te-based composite film. Here, we show that while applying Selective Metallization Technique, the evaporation of metal modifies the impact of residual oil on Bi-Sb-Te, which can be effectively removed with a few seconds of plasma exposure, and the fabricated thermoelectric devices are validated in wearable applications utilizing a coiled-up wristband design.